The role of commitment to learning in the effect of evaluation and rewards on project success in R&D teams - Aşçı, Mehmet Saim; Civelek, Mustafa Emre; Çemberci, Murat (My University, 2020)
In enterprises, Research and Development (R&D) activities are carried out on the basis of projects. R&D projects are conducted by teams of employees from the different departments in an enterprise. Members of R&D teams have different competencies, and the most prominent features are that they are creative and learning-oriented. Despite the competencies of the employees, it is very difficult to manage such teams successfully. Keeping the motivation of team members high and managing the team in a success-oriented way require important managerial skills since such teams have many different sources of motivation. Therefore, team leaders need to identify the factors that will lead their R&D teams to success. Accordingly, this paper attempts to explain the role of commitment to learning on the relationship between evaluation-rewards and project success. The mediator analyses were conducted according to the methodology suggested by Baron and Kenny. As a result of the hypothesis tests, it has been found out that commitment to learning has a mediator effect on the relationship between evaluation and reward and project success. In R&D teams, team members' commitment to learning is critical to the impact of reward and evaluation on project success. Therefore, the leaders who will lead these teams need to consider the nature of an adhocratic organization while taking into account the factors that will influence team success.
Keywords: Commitment to Learning; Evaluation and Rewards; Project Success; Team Working; R&D Teams